2016
DOI: 10.1515/ael-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure on Related Party Transactions: Evidence from Italian Listed Companies

Abstract: Recent shortcomings in corporate affairs, related to the bursting of the New Economy Bubble and the global financial crisis, have forced regulators to strengthen current rules introducing new bans and requirements, aimed at guaranteeing the substantial and economic fairness of related party transactions (RPTs). In 2010 rules regarding RPTs were completely reshaped by the Italian Regulatory Body for the Italian Stock Exchange (CONSOB Regulation no. 17221). One of the most important amendments regarded the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Assonime reports annually on formal compliance with the Code, and it revealed a widely spread adhesion to it by (close to) all Italian listed companies. However, several studies (Bava & Di Trana, ; Bianchi et al, ; Bianchi, Ciavarella, Novembre, & Signoretti, ) found that Italian listed companies are not effectively compliant with the Code's recommendations, showing a gap between formal and effective compliance. Bava and Di Trana (, p. 144) found that the Regulation increased the amount of information disclosed to the market, but “the percentage of their magnitude on the gross amount is worryingly low.” Bianchi et al (, p.108) stated that “the adoption by Italian companies of best practices for dealing with potential conflicts of interests in RPTs is markedly weaker than what is formally declared in the reports”.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Assonime reports annually on formal compliance with the Code, and it revealed a widely spread adhesion to it by (close to) all Italian listed companies. However, several studies (Bava & Di Trana, ; Bianchi et al, ; Bianchi, Ciavarella, Novembre, & Signoretti, ) found that Italian listed companies are not effectively compliant with the Code's recommendations, showing a gap between formal and effective compliance. Bava and Di Trana (, p. 144) found that the Regulation increased the amount of information disclosed to the market, but “the percentage of their magnitude on the gross amount is worryingly low.” Bianchi et al (, p.108) stated that “the adoption by Italian companies of best practices for dealing with potential conflicts of interests in RPTs is markedly weaker than what is formally declared in the reports”.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, several studies (Bava & Di Trana, 2016;Bianchi et al, 2014;Bianchi, Ciavarella, Novembre, & Signoretti, 2011) found that Italian listed companies are not effectively compliant with the Code's recommendations, showing a gap between formal and effective compliance. Bava and Di Trana (2016, p. 144) found that the Regulation increased the amount of information disclosed to the market, but "the percentage of their magnitude on the gross amount is worryingly low."…”
Section: Legal Protection Of the Minority Shareholders And Rpts In Italymentioning
confidence: 99%
“…Firms and corporations are at liberty to adopt any prevailing codes to suit their business requirements. This statement is especially true when the regulator issues enabling rules that are aimed to increase transparency in RPT and to reduce the tendency of a conflict of interest therein (Bava & Di Trana, 2016). As such, disclosure is known as an effective tool in corporate governance since it is present in many non-mandatory guidelines or rules issued by regulators all over the world.…”
Section: Mandatory/enabling Theorymentioning
confidence: 99%
“…However, as yet, the literature on RPTs has not paid enough attention to the relationship between CG and RPT disclosure, although the knowledge of these transactions can affect the way in which analysts of financial statements assess the performance, financial position and risk and opportunities of an entity (Corlacio and Tudor, 2011). Current rules on RPTs must be revised and improved because of a lack of efficiency (Gromis di Trana, 2014;Bava and Gromis di Trana, 2015a).…”
Section: Rpts and Cgmentioning
confidence: 99%